Factors Affecting Work Performance among Nurses in Delivering Health Service for the National Health Insurance Patients at Dr. Moewardi Hospital, Surakarta - Nureesa Doloh; Didik Tamtomo; Endang Sutisna Sulaeman (Journal of Health Policy and Management, 2018)
Background: The performances of the doctors and the nurses are especially important in accomplishing health care in a continuous and effective way. It is important to examine all organizational, individual, social factors that especially affect the performances of the doctors and nurses holistically. The purpose of this study was to assess factors affecting work performance among nurses in delivering health service for the national health insurance patientsat Dr. Moewardi Hospital, Surakarta.Subjects and Method: A cross-sectional study was carried out in Dr. Moewardi Hospital, Surakarta, Central Java. A sample of 150 nurseswho provided health services to the National Health Insurance patientswas selectedfor this study by proportional random sampling. The dependent variable was work performance. The independent variables were work satisfaction, work motivation, and supervision. The data were collected by questionnaire and analyzed by path analysis run on Stata 13.Results: Work performance was affected by work satisfaction (b=0.88; 95%CI=0.05 to 1.71; p=0.037), work motivation (b=0.81; 95%CI=-0.06 to 1.68; p=0.070), and supervision (b=0.97; 95%CI=0.18 to 1.76; p=0.016). Work performance was also indirectly affected by motivation. Conclusion: Work performance is affected by work satisfaction, work motivation, and supervision. Work performance is also indirectly affected by motivation.Keywords: work performance, motivation, supervision, satisfaction, nursesCorrespondence: Nureesa Doloh. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 336 A, Surakarta 57126, Central Java.Email: nursenuris2015@gmail.com.Mobile:+62895414785888.Journal of Health Policy and Management (2018), 3(1): 20-25https://doi.org/10.26911/thejhpm.2018.03.01.03